(untitled) (Journal of Applied Learning and Teaching, 2025)
This research explores the transformative potential of drama pedagogies in medical education by developing and implementing a creative drama-based curriculum aimed at enriching medical students’ patient communication skills. The study integrates the Source-Message-Channel-Receiver Model of Communication and Cognitive Learning Theory within a framework of applied theatre practices to address this often-overlooked aspect of medical training in Thailand. Field research was conducted with a purposively selected group of twenty-two first-year medical students at a Thai university in two stages: 1) the creation of a drama-based educational intervention and 2) its subsequent evaluation using an observational assessment method. The researchers designed a series of drama activities, which were taught over six sessions, each lasting two hours. The first half of the programme introduced fundamental principles of the dramatic process, while the second half applied these processes directly to medical contexts. This structure aimed to develop two primary communication abilities: empathy and public speaking. Post-intervention evaluation revealed a substantial improvement in the participants’ communication skills. This enhancement was evident across all evaluated areas and bore statistical significance at the 0.01 level. This study demonstrates the efficacy of applied theatre practices in fostering essential communication skills within medical education, an approach relatively rare in the didactic environment of Thai universities. It emphasizes the potential for theatre-based pedagogical interventions to facilitate cultural engagement, education, and social change, thereby promoting the development of innovative teaching methods for medical students.